Le monde romain et l’histoire environnementale. Perspectives et enjeux face à une crise écologique globale - Marguerite Ronin (Les Cahiers de Framespa)
Ancient Environmental History is not yet a clearly identified field of study in France and this article aims at demonstrating the potentialities of the Roman Empire to open new avenues of research in this perspective. It also argues that the Roman world can be used as a methodological tool to better contextualize the current ecological crisis by helping us shape the questions we address to our own world concerning, for example, the exhaustibility of the natural resources and the solutions developed for their exploitation. In particular, the imperialistic dimension of Rome strongly resonates with modern and contemporary examples of natural resources control. This article further argues that the Roman legal model, still existent in a good part of the juristic solutions applied to the management of the natural environment in many countries throughout the world, needs to be investigated in its historical dimension and some aspects of it revisited.